(untitled) (Research, Society and Development, 2020)
The objective of this work is to evaluate the influence of different concentrations of tiririca extract on the rooting of fig cuttings in different shading screens. The experiment was conducted in the experimental area of Forestry of the State University of Mato Grosso in Cáceres-MT. The design adopted was in randomized blocks in a 2 x 5 factorial scheme in 4 replications, being 2 environments: red chromatinet screen and thermoreflector screen and 5 concentrations of tiririca extract (0, 2.5, 5.0, 7.5 and 10%). The parameters evaluated were number of shoots per cutting, percentage of rooted cuttings; number of roots per cutting; length of the largest root, fresh mass and dry mass of the roots. The data were submitted to variance analysis and the means compared by the Tukey test, with the SISVAR program. There was no interaction between the studied environments and the different doses of tiririca extract. The red chromatinet shading screen provided a greater number of shoots in fig cuttings up to 45 days after planting, and promoted a greater number of roots. The concentrations of tiririca extract studied do not influence the production of fig seedlings.